Design and assessment of a new helical fixed bed type CO2 methanation reactor. (1st April 2023) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Highlights: The three proposed helical fixed bed reactors are capable of reducing the reactor temperatures and performing well overall. All reactor models were able to be cooled adequately with coolant temperature 200 °C. Reactor Concept 1 was able to achieve CH4 yield of 87%. Reactor Concept 1 was able to achieve H2 and CO2 conversion of 75%. Abstract: In the present study, new designs of helical methane/natural gas reactors are proposed. The reactor harnesses the Sabatier reaction, in which CO2 reacts with H2 gas to produce methane. The CO2 and H2 used within the reactor can be produced through biomass gasification and electrolysis, thereby making the process renewable. The study develops three models with three diameters (0.0254 m, 0.0318 m, and 0.0381 m) and the same volume (0.001 m 3 ). The helical methane reactor design can be optimized by varying specific parameters, such as the reactor inlet temperature, cooling temperature and inlet pressure. Most notably, the reactor model with a diameter of 0.0381 m can produce a reactant conversion and a yield of 75% and 87%, respectively. Additionally, the model having a cross-sectional diameter of 0.0254 m is capable of being cooled most effectively when a coolant temperature of 200 °C is considered.